The planktonic ostracods of the Cariaco Trench and adjacent waters - Deevey, G. B. (Proceedings of the Biological Society of Washington, 1978)
Sampling was carried out at 3 stations; at Station 11 at 10 degree 29'N, 64 degree 26'W in the Cariaco Trench off Cumana, at Station 63, an inshore station, at 11 degree 14'N, 65 degree 00'W, and at Station 76, an offshore station at 11 degree 45'N, 66 degree 56'W. Of 50 species of ostracod recorded from the 3 stations, only 10 were found at Station 11 (compared to 45 at Station 63 and 44 at Station 76). The Cariaco Trench is a depression up to 1,400 m deep in the continental shelf off noth Venezuela, that is anaeobic beneath 300 and 400 m. The ostracod species found in the sampling programme are reviewed, including a description of the new species Archiconchoecia fabiformis